2011
DOI: 10.1534/genetics.111.129353
|View full text |Cite
|
Sign up to set email alerts
|

A Balance Between Euchromatic (JIL-1) and Heterochromatic [SU(VAR)2-5 and SU(VAR)3-9] Factors Regulates Position-Effect Variegation inDrosophila

Abstract: In this study, we show that the haplo-enhancer effect of JIL-1 has the ability to counterbalance the haplo-suppressor effect of both Su(var)3-9 and Su(var)2-5 on position-effect variegation, providing evidence that a finely tuned balance between the levels of JIL-1 and the major heterochromatin components contributes to the regulation of gene expression.T HE essential JIL-1 histone H3S10 kinase (Jin et al. 1999;Wang et al. 2001) is a major regulator of chromatin structure (Deng et al. 2005(Deng et al. , 2008) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 24 publications
(38 reference statements)
5
31
0
Order By: Relevance
“…Therefore, these findings provide additional evidence that such parameters are probably independent of, and separate from, the mechanisms of classical heterochromatin assembly and gene silencing. This hypothesis is supported by experiments probing for dynamic interactions between loss-of-function alleles of JIL-1 and Su(var)3-9, Su(var)3-7 or Su(var)2-5 using PEV assays (Deng et al, 2010;Wang et al, 2011), where a direct antagonistic and counterbalancing effect on gene expression between JIL-1 and all three heterochromatic factors has been demonstrated.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Therefore, these findings provide additional evidence that such parameters are probably independent of, and separate from, the mechanisms of classical heterochromatin assembly and gene silencing. This hypothesis is supported by experiments probing for dynamic interactions between loss-of-function alleles of JIL-1 and Su(var)3-9, Su(var)3-7 or Su(var)2-5 using PEV assays (Deng et al, 2010;Wang et al, 2011), where a direct antagonistic and counterbalancing effect on gene expression between JIL-1 and all three heterochromatic factors has been demonstrated.…”
Section: Discussionmentioning
confidence: 78%
“…PEV assays were performed as previously described Bao et al, 2007;Deng et al, 2010;Wang et al, 2011). In short, we generated flies expressing the various JIL-1 constructs in a background of the two PEV arrangements (118E-10 or w m4 ) by standard crossing.…”
Section: Drosophila Melanogaster Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, we observed that the mutation in Su JIL-1 is a multidomain protein responsible for the phosphorylation of the histone H3, as well as maintenance of the structure of the polytene chromosomes in Drosophila. JIL-1 LoF alleles have a strong effect on PEV, and JIL-1; Su(var) 205 and JIL-1; Su(var)3-9 double mutants show enhanced variegation (Wang et al 2011). This indicates that reduced dosage of JIL-1 can counterbalance the typical suppressive effect of HP1 and Su(var)3-9 on PEV.…”
Section: Su(var)205 and Mod(mdg4) Are Dominant Suppressors Of Pev Regmentioning
confidence: 99%
“…JIL-1 has histone kinase activity (Jin et al 1999;Rath et al 2006;Zhang et al 2006) and is involved in the negative regulation of chromatin silencing and in chromosome organization. Deficiency of JIL-1 leads to strong enhancer of variegation (white-eye phenotype), counteracting even the suppressor-of-variegation effect of HP1 and Su(var)3-9 (Wang et al 2011).…”
mentioning
confidence: 99%